Negotiating Childhoods : Applying a Moral Filter to Children's Everyday Lives - Frankel, Sam (Studies in Childhood and Youth, 2017)
This book investigates how constructed representations of the child have and continue to restrict children's opportunities to engage in moral discourses, and the implications this has on children's everyday experiences. By considering a moral dimension to both structure and agency, the author focuses on the nature of the images that are used to represent the child and how these sit in contrast to the active and meaning-driven way in which children negotiate their everyday lives. The book therefore argues that 'morality' provides a filter to understand the backdrop for interaction, as well as offering a focus for engaging with the individual as a social agent, acting and reacting in the world around them. Negotiating Childhoods will be of interest to students and scholars of sociology, childhood studies, criminology, social work, culture and media studies and philosophy.- Resumé vydavatel.